Assessment of Nurse–Midwives' Knowledge and Practices toward Second Stage of Labor - Rasheid, ahrar; ali, Rabea'a (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To assess the nurses-midwives' knowledge and practices regarding the management of second stageof labor and to find out the association between their knowledge and practices and socio-demographiccharacteristics and working years and experience.Methodology: A descriptive study was carried out from March 22nd, 2008 through 30th June, 2008. A purposivesample of (75) Nurse-Midwives which was selected from (6) hospitals. A questionnaire was comprised of twoparts: (socio-demographic characteristics and the assessment tool for Nurse-Midwives' knowledge and healthpractices performed by them). The questionnaire validity was determined by experts and its reliability wasdetermined through a pilot study. The correlation coefficient was (0.90) for knowledge and (0.83) for practices.Data were collected through interview and observational tool and analyzed through the application of descriptiveand inferential statistical approaches.Results: The study findings indicated that there was a high mean of scores in Nurse-Midwives' knowledge and alow mean of scores for their practices in most of the items regarding second stage of labor. The study findingsalso indicated that there is a significant association between nurses-midwives' practices and their educationallevel, and birth number average.Recommendations: The study recommends that; installing in-service educational program for Nurse-Midwivesto upgrade the techniques necessary to assess, evaluate and improve the quality of care rendered to laboringwomen, and to put an emphasis on the Ministry of Health to conduct training course for the Nurse-Midwives inorder to change their malpractices and updating their knowledge with regular supervision on their performance.